Forensic determination of adhesive vinyl microplastics in urban soils - Sebastião, Glaucia Isabel de Andrade (Universidade Federal de São Carlos, 2024)
Plastic production and consumption hubs are mainly concentrated in large urban centers, causing the soil in these places to become large sinks of fragments generated from their breakdown, known as microplastics (MPs). Adhesive vinyl polymers, widely used in various commercial sectors, as far as we know, have never been investigated scientifically from the perspective of their potential to form MPs. This proof-of-concept work started by studying the soil around a plaque made of adhesive vinyl that had been exposed to the weather for 8 years and was visibly degraded. We customized a selective methodology for separating specific MPs from the soil and obtained a range of 5.8×103 fragments kg-1 of dry soil being produced from a maximum of 1 cm² of adhesive vinylfilm. In addition: (1) it was observed that vertical and horizontal transport was not favored, causing the formation of a great potential for hotspots; (2) the area of the fragments did not influence vertical transport. Here, we presented a forensic assessment for the association between the presence of MPs and its source.
Determinação forense de microplásticos vinílicos em solos urbanos
Keywords: Soil contamination; Microplastic hotspot; Sticker; Weathering material; Density separation; Contaminação de solo; Hotspot de microplásticos; Adesivo; Material intemperizado; Separação por densidade; CIENCIAS BIOLOGICAS